2019
DOI: 10.3847/1538-4357/ab2ecf
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Order Estimation of the Speckle Electric Field History for Space-based Coronagraphs

Abstract: In high-contrast space-based coronagraphs, one of the main limiting factors for imaging the dimmest exoplanets is the time varying nature of the residual starlight (speckles). Modern methods try to differentiate between the intensities of starlight and other sources, but none incorporate models of space-based systems which can take into account actuations of the deformable mirrors. Instead, we propose formulating the estimation problem in terms of the electric field while allowing for dithering of the deformab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The authors have previously suggested that combining dark hole maintenance with EFOR could lead to smaller errors in post-processing. 18 Below, we re-assess this claim in the presence of jitter and high order DM drift (i.e., when each actuator drifts independently of all others). To this end, we use the data simulated in Sec.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have previously suggested that combining dark hole maintenance with EFOR could lead to smaller errors in post-processing. 18 Below, we re-assess this claim in the presence of jitter and high order DM drift (i.e., when each actuator drifts independently of all others). To this end, we use the data simulated in Sec.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The authors have also previously suggested that known DM perturbations introduced during a closed-loop observation phase can be exploited in post-processing. In section 3, we extend Electric Field Order Reduction (EFOR 18 ) to incorporate images taken at different telescope orientations and subtracts the contribution of the jitter (by identifying a small number of fast-varying jitter modes).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods rely on performing principal component analysis (PCA) on reference observations of a calibration star similar to the host star, but without astrophysical companions, to calibrate out residual static or quasi-static starlight (Lafrenière et al 2007;Soummer et al 2012;Pueyo 2016). Additional sources of information on residual WFE include telemetry from wave front sensing and control (WFSC) systems such as wave front sensor residuals (Vogt et al 2011) or focal-plane electric field estimates (Pogorelyuk et al 2019), data from a self-coherent camera (Baudoz et al 2006), and data at different wavelengths as exploited in spectral deconvolution (Sparks & Ford 2002).…”
Section: Introductionmentioning
confidence: 99%
“…6 The performance of such methods depends heavily on the size of the patterns library (i.e., number of intensity modes), which scales unfavorably with the dimensionality of the pre-coronagraph wavefront perturbation (e.g., the number of Zernike polynomials describing the wavefront error in the pupil plane). 7 Other intensity-based approaches, exploit the difference in the physical behavior of speckles and sources incoherent with the starlight (e.g., planets). Angular Differential Imaging (ADI) 8 rotates the images such that the speckles, that are (at least partially) fixed to the telescope, self-subtract, while the incoherent sources that do not rotate with the telescope persist.…”
Section: Introductionmentioning
confidence: 99%